Teologia biblica come teologia della Bibbia - Bourgine, Benoît (Teologia, 2023)
The article deals with the relationship between biblical theology and the theology of the Bible. First of all, it is necessary to clarify what "biblical theology" means, and this will be done thanks to the definition given by an exegete, Paul Beauchamp, and a dogmatist, Karl Barth. Secondly, it is necessary to mark the difference between biblical theology and the theology of the Bible: here my main intention is to show what the theology of the Bible can do that biblical theology cannot do; and vice versa, what biblical theology can do that biblical theology cannot do. Third, I would thus like to explain how biblical theology is justified in claiming continuity and interaction with the theology of the Bible. Finally, fourth and last point, I would like to clarify what interest there may be in supporting this affinity and considering biblical theology as the heart of the theological act: the correctness and unity, vitality and fruitfulness of all theology are at stake. (English)